MENINGKATKAN KEMAMPUAN PENGUASAAN KONSEP DAN METODE PEMBELAJARAN MATEMATIKA DENGAN PAIKEM BERBASIS ICT BAGI GURU MADRASAH IBTIDAIYAH (MI) - Yulia Romadiastri (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2016)
To improve the quality of mathematics learning, Madrasah Ibtidaiyah in district Ngaliyan has conducted various types of activities, one of the efforts was to form a working group on teachers (KKG). As a result, madrasah teacher empowerment especially in mathematics learning both in concept and mastery learning methodologies are not as expected. KKG as formal institution that hosts MI teachers need to be empowered with the support of various parties. Problems occurred was a classroom teacher MI less mastered the concept of integrative mathematics so there was some misconception of the material and they also has limited knowledge of the variation of mathematics learning method in a fun, meaningful and engaging the liveliness of the learners according scientific approach. The phases program public service performed are: (1) brainstorming and (2) training. The result of these outreach programs include: training PAIKEM Learning and Contextual ICT Media for the teachers who are members of KKG MI Subdistrict Ngaliyan goeswell. Participants who attend the training look very enthusiastic because theyrarely get similar training.From the results of training obtained by awide range of new knowledge about learning math in an active and funway. Producing a contextual ICT media for learning mathematics. Brainstorming is done against the commitee of KKG MI Ngaliyan and greeted with enthusiasm, especially with the offer of assistance and cooperation with the Department of Mathematics Education of the Faculty of Science and Technology UIN Walisongo Semarang.